INFLUENCE OF RELAXATION THERAPY (ROSE AROMATHERAPY) TOWARDS BLOOD PRESSURE CHANGE OF THE ELDERLY WITH HYPERTENSION - Kenia, Ni Made; Taviyanda, Dian (Jurnal Penelitian STIKES Kediri, 2013)
The relaxation therapy (rose aromatherapy) is one of hypertension therapy. The objective of this research was to analyze influence of relaxation therapy (rose aromatherapy) towards blood pressure changes. The design was queasy experiment. The population was elderly with hypertension, the samples were 44 respondents using purposive sampling technique. The research variable was blood pressure. Data was collected using mercury sphygmomanometer, to determine the influence of relaxation therapy (rose aromatherapy). The analysis Â using paired sample t-test and independent t-test with significant level Î±<0.05. The result showed that systolic and diastolic of blood pressure decreased significantly (p=systolic=0.000 and p=diastolic=0.000). Relaxation therapies (rose aromatherapy) for 10 minutes could decrease systolic of blood pressure and diastolic of blood pressure, with mean value decreasing systolic and diastolic were 10.63 mmHg and 10.18 mmHg and maximal value of Â decreasing systolic and diastolic were 28.00 mmHg and 20 , 00 mmHg. The conclusion of this research is there was a significant influence of relaxation therapy (rose aromatherapy) towards blood pressure changes to the elderly with hypertension.